Factors influencing implementation of food and food-related waste audits in hospital foodservices - Cook, Nathan; Collins, Jorja; Goodwin, Denise; Porter, Judi (Frontiers in Nutrition, 2022)
Background Designing a food waste audit tool for novel hospital foodservice practice does not guarantee uptake. Intended users must be consulted to understand the tool’s feasibility and face validity. This study aimed to identify the perspectives of staff involved in the operation of hospital foodservices on (1) how an evidenced based consensus pathway food waste audit tool is perceived to translate into practice, and (2) to determine the factors that influence the completion of food and food-related waste audits within this setting. Materials and methods Purposeful sampling was used to recruit staff with knowledge on the operation/governance of foodservices within hospitals in Victoria, Australia. Semi-structured interviews (n = 20) were conducted via Zoom to explore barriers and enablers to completing food and food-related waste audits and a previously published food waste audit tool. NVivo was used for inductive thematic analysis. Results Three factors determined the completion of food and food-related waste audits in hospital foodservices, and each factor could be a barrier or an enabler; (1) capacity: the availability of time, labour and materials to complete an audit (2) change: staff resistance to audit procedures and how to gain their buy-in (3) processes, governance, and leadership: the opportunity for high level support, policy and structure to encourage waste audits if present. The consensus tool appeared to have face validity. Planning audit operations, conducting stakeholder meetings, providing education/training to foodservice team members, and facilitating communication between managers and staff were described to support consensus tool use and audit completion. Conclusion The consensus tool can be used to support hospital foodservices to complete food and food-related waste audits, although it may need to be customised to be fit for purpose. Optimising the capacity, change management and processes, governance and leadership of the foodservice department may improve the experience and success of a food and food-related waste audit.